2002
DOI: 10.1086/338319
|View full text |Cite
|
Sign up to set email alerts
|

The Extent of NGC 6822 Revealed by Its C Star Population

Abstract: Using the CFH12K camera, we apply the four band photometric technique to identify 904 carbon stars in an area 28 ′ × 42 ′ centered on NGC 6822. A few C stars, outside of this area, were also discovered with the Las Campanas Swope Telescope. The NGC 6822 C star population has < I > = 19.26 leading to a < M I > = -4.70, a value essentially identical to the mean magnitude obtained for the C stars in IC 1613. Contrary to stars highlighting the optical image of NGC 6822, C stars are seen at large radial distances a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
193
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(209 citation statements)
references
References 38 publications
13
193
3
Order By: Relevance
“…Furthermore, a recent M 31 outer disk survey, using Sloan r , g and i filters, also suggests that bright C stars are lacking in the outskirt of the disk (Demers & Battinelli, in preparation). Such magnitude trend is also seen in NGC 6822 (Letarte et al 2002), albeit less pronounced because of the much shorter distance range. The bright limit of the apparent magnitudes of the LMC C stars, compiled by Kontizas et al (2001) shows, likewise, an obvious radial trend, over some 8 degrees.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Furthermore, a recent M 31 outer disk survey, using Sloan r , g and i filters, also suggests that bright C stars are lacking in the outskirt of the disk (Demers & Battinelli, in preparation). Such magnitude trend is also seen in NGC 6822 (Letarte et al 2002), albeit less pronounced because of the much shorter distance range. The bright limit of the apparent magnitudes of the LMC C stars, compiled by Kontizas et al (2001) shows, likewise, an obvious radial trend, over some 8 degrees.…”
Section: Discussionmentioning
confidence: 58%
“…The zero-point of the narrow band observations was obtained setting the average (CN-TiO) of blue stars equal to zero following a procedure similar to what adopted by Brewer et al (1995). This procedure is explained by Letarte et al (2002) and in the present paper we follow their definition of blue stars as stars in the colour range 0.0 < (R − I) 0 < 0.45. To convert observed (R − I) colours into intrinsic colours we adopt E(B − V) = 0.10 corresponding to the value for the SW2 field of Battinelli et al (2003).…”
Section: Discussionmentioning
confidence: 99%
“…Candidate C-and M-type AGB stars were classified on the basis of their magnitudes and NIR colours to obtain the C/M ratio. However, a comparison of the classifications in Paper I with those in the work of Letarte et al (2002), who relied on the CN-TiO method to classify sources, suggested that up to ∼20% of the C-type star population may have been misclassified as M-type stars by the derived JHK criteria. A review of the estimated error in source classification in Paper I and the level of misclassification in the catalogue of Letarte et al (2002), which was previously assumed to be 100% accurate, are therefore the secondary and tertiary aims of this work.…”
Section: Aims Of This Papermentioning
confidence: 94%
“…However, a comparison of the classifications in Paper I with those in the work of Letarte et al (2002), who relied on the CN-TiO method to classify sources, suggested that up to ∼20% of the C-type star population may have been misclassified as M-type stars by the derived JHK criteria. A review of the estimated error in source classification in Paper I and the level of misclassification in the catalogue of Letarte et al (2002), which was previously assumed to be 100% accurate, are therefore the secondary and tertiary aims of this work. Using spectra of a sample of candidate C-and M-type AGB stars common to the catalogues of Paper I and Letarte et al (2002), the present work is the first to use spectra to examine sources that have been classified using both JHK photometry and CN-TiO data, with the object of quantifying the level of error associated with each technique.…”
Section: Aims Of This Papermentioning
confidence: 94%
“…Its optical structure is dominated by a bar that is 8 long (about 1.1 kpc), oriented almost N-S, and it contains a huge disk of H  of about 6 × 13 kpc at a position angle (PA) of 130 • centred on the optical centre (de Blok & Walter 2000;Weldrake et al 2003). In addition, a huge spheroidal stellar distribution with its long axis at PA of 64.5 • (almost perpendicular to the H  disk), composed mainly of intermediate-age stars, has been found (Letarte et al 2002;Battinelli et al 2006). Interestingly, the H  disk and the stellar spheroid do not share the same kinematics.…”
Section: Introductionmentioning
confidence: 99%